LARANGAN PERNIKAHAN SESAMA SUKU MELAYU RIAU DALAM PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF (Studi kasus di Desa Lubuk Terap, Kecamatan Bandar Petalangan, Kabupaten pelalawan, Provins - Wahyu Agung Dwi Putra; Miftah, Ahmad Harisul (Program Studi Hukum Keluarga dan Hukum Ekonomi Syariah, Program Pascasarjana Institut Agama Islam Negeri (IAIN) Ternate, 2023)
Marriage and adat are closely related to Malay tribal customs because ninik-mamak or traditional elders play an important role in wedding planning. The recommended marriage is back to bako, where a man marries the nephew of his maternal uncle, this is the ideal marriage according to the Petalangan people. There are other restrictions on marriages among the Petalangan tribe, one of which is that partners cannot come from the same matrilineal clan (tribe). Since ancient times, there has been a ban on same-ethnic marriage, and some argue that breaking this rule can be fatal. People who do not comply with these rules face customary punishments, such as fines or expulsion from the Petalang tribe. In addition, this is in accordance with the decision of the traditional elders or ninik-mamak. This research is field research with a descriptive qualitative type of research with empirical and normative juridical approaches. This research concludes that: 1. The practice of marriage among the Malays in Lubuk Terap Village still follows the customary rules that have existed since the time of their ancestors. 2. The prohibition on same tribe Malay marriages in Lubuk Village has been around since ancient times. 3. There are no verses in the Qur'an and Hadith that oblige or prohibit same tribe marriage, as well as positive law marriage regulations. In the Indonesian legal system, such as the Islamic Law Compilation (KHI), there is also no prohibition on same tribe marriages. Because of this the law of carrying out this marriage is permissible. In addition, this rule does not apply to the general public, but only to the Malays in Riau.